The future of insolvency law in a post-pandemic world - Aurelio GURREA-MARTINEZ (Institutional Knowledge at Singapore Management University, 2022)
The COVID-19 crisis has encouraged many countries to amend their insolvency laws. In most cases, these amendments took place temporarily, especially during the hibernation phase of the pandemic. In other countries, however, the pandemic has led to permanent changes in their insolvency legislation. More importantly, the COVID-19 crisis has accelerated the insolvency reforms that were already on the political agenda of many countries, and it has encouraged other jurisdictions to reassess the desirability of their insolvency and restructuring frameworks. This article analyses the current trends, reforms and policy discussions that are expected to reshape the future of insolvency law in a post-pandemic world.